Crisis in today’s time: The impact of situational crisis communication theory & strategies towards the crisis response outcomes of food & beverage companies in the Philippines - Briones, Paulo Raphael Lim (Animo Repository, 2023)
The Situational Crisis Communication Theory (SCCT) was developed by Timothy Coombs in 1994 wherein the author discusses how communication is essential in the process of dealing with a crisis. The main problem of the study is to find out how the theory supports a company in the Philippine food & beverage industry in their ability to respond to crises with regard to timeliness, credibility, reputation, and trustworthiness. In order to find the answer to this problem, the researchers used an Input-Procedure-Output framework, where the researchers utilized surveys and key informant interviews (KIIs) in order to find the relationship between crisis history and responsibility attribution and its positive impacts to crisis response outcomes. Through descriptive analyses and correlation matrices, the researchers were able to find out that both of the said variables have varying results per company where findings showed a perfect correlation and a weak positive correlation. However, overall findings suggest a positively strong and significant relationship with the timeliness, credibility, and organizational reputation and trustworthiness of the combined result of the companies being studied. The researchers recommend that the SCCT is to be integrated in the company’s operations to maximize productivity and hone decision-making skills during a crisis. Key words: crisis management, situational crisis communication theory, timeliness, credibility, organizational reputation, trustworthiness